ANALYSIS OF MEDICAL RECORD RECORDING OF MEDICAL INTENSIVE PATIENTS MIDWIFE HASRI AINUN HABIBIE HOSPITAL IN 2020: ANALYSIS OF MEDICAL RECORD RECORDING OF MEDICAL INTENSIVE PATIENTS MIDWIFE HASRI AINUN HABIBIE HOSPITAL IN 2020 - sau, rahmawati; Muhammad Isman Jusuf; Adnan Malaha (Governance: Jurnal Ilmu Administrasi Publik, 2023)
The aims of this study were: 1) to analyze the medical records of inpatient obstetrics at Hasri Ainin Habibie Hospital; 2) find out what factors affect the recording of medical records at the Hasri Ainun Habibie Hospital. This study uses a descriptive qualitative approach. Primary data obtained through interviews. Data processing techniques in this study are qualitative data analysis techniques, by doing data reduction, data presentation and conclusions and verification. Testing the validity of the data is done by triangulation of sources. The results showed that: 1) the absence of medical physical examination items in the monthly report notes of midwifery inpatient medical records at the Hasri Ainun Habibie Hospital; 2) there are still medical record data that are not filled in on time according to the standards of the Minister of Health; 3) there are several medical record documents that are still often returned from the medical record installation to the midwifery inpatient medical record administration room; 4) medical record administration staff are still chasing doctors to fill in the completeness of medical records that have been returned from the medical record installation; 5) there are still medical record documents that have not been fully covered in the monthly report; 6) medical record coordinator is not qualified from medical record; 7) Of the 27 medical record personnel only 2 qualified from medical records; 8) there are still medical records personnel with educational qualifications from high school; 9) the absence of STR on medical record personnel; 10) medical record facilities and infrastructure at Hasri Ainun Habibie hospital are not yet complete; 11) Lack of socialization regarding the SOP for medical resumes.